Race, Law, and "The Chinese Puzzle" in Imperial Britain - Auerbach, S. author. aut Link
XII, 268 p.
Keywords: In the early twentieth century, Chinese immigration became the focal point for racial panic in Britain. Fears about its moral and economic impact - amplified by press sensationalism and lurid fictional portrayals of London's original 'Chinatown' as a den of vice and iniquity - prompted mass arrests, deportations, and mob violence. Even after the neighborhood was demolished and its inhabitants dispersed, the stereotype of the Chinese criminal mastermind and other 'yellow peril' images remained as permanent aspects of British culture. This painstakingly researched study traces the historical evolution of Chinese communities in Britain during this period, revealing their significance in the development of race as a category in British culture, law, and politics.